Comparison of four active SARS-CoV-2 surveillance strategies in representative population sample points: two-factor factorial randomized controlled trial - Deckert, Andreas; Anders, Simon; Morales, Ivonne; De Allegri, Manuela; Nguyen, Hoa Thi; Souares-Coutant, Aurélia; McMahon-Rössle, Shannon A.; Meurer, Matthias; Burk, Robin; Lou, Dan; Brugnara Kirchmann, Lúcia; Sand, Matthias; et al. (JMIR public health and surveillance, 2023)
Background: The COVID-19 pandemic is characterized by rapid increases in infection burden owing to the emergence of new variants with higher transmissibility and immune escape. To date, monitoring the COVID-19 pandemic has mainly relied on passive surveillance, yielding biased epidemiological measures owing to the disproportionate number of undetected asymptomatic cases. Active surveillance could provide accurate estimates of the true prevalence to forecast the evolution of the pandemic, enabling evidence-based decision-making.